Identification of Czech Metropolitan Regions: How to improve targeting of innovation policy - Klímová, Viktorie; Žítek, Vladimír (Naše gospodarstvo/Our economy, 2016)
Concepts of national and regional innovation systems can serve as an analytical framework forming the empirical base for innovation policy creation. It is possible to distinguish various types of these systems. One of these typologies is based on the assessment of innovation deficiencies. There are three types of regions: metropolitan, peripheral, and old industrial. Metropolitan regions can be characterized by a high level of research, innovation, and patent activity. The aims of this paper are to find relevant indicators that can be used as the basis for defining metropolitan regional innovation systems and using them for the identification of Czech metropolitan regions. The results of the point method combined with the cluster analysis showed that the capital city, Prague, as well as the South Moravian, Pardubice, Central Bohemian, Pilsen, and Liberec Regions can be defined as metropolitan regions.